Habilidades sociales en niños y niñas de cinco años de instituciones educativas de la Red N° 4 del distrito Callao - Ballena Gómez, Ana Cecilia (2010)
This comparative descriptive study was to determine whether there are differences in social skills among children 5 years of educational institutions in the Red District No. 4 of Callao. Participants were 109 children of low socioeconomic status, which were randomly selected: 55 girls and 54 boys. The instrument applied was the Scale of Assessment of Social Skills in Childhood, by teachers. The results showed no significant differences between boys and girls in regard to basic social skills, social interaction, skills for the initiation of social interaction and conversational skills, sharing and cooperation skills, abilities related to emotions and feelings or the skills of selfassertion.